Chitosan induces jasmonic acid production leading to resistance of ripened fruit against Botrytis cinerea infection - Peian, Zhang; Haifeng, Jia; Peijie, Gong; Sadeghnezhad, Ehsan; Qianqian, Pang; Tianyu, Dong; Teng, Li; Huanchun, Jin; Jinggui, Fang (Food chemistry, 2021)
•Chitosan inhibited the mycelial growth of Botrytis cinerea and protected the fruit quality.•Jasmonic acid (JA) biosynthesis-associated genes were up-regulated by chitosan in Botrytis cinerea-infected grapes.•TPR3 and HDAC19 were identified by data‐independent acquisition (DIA) measurement that changed in response to chitosan.•Chitosan and JA increased resistance to pathogenesis in ripened grape fruits through down-regulation of TPR3 and HDAC19. Chitosan can function a key role in plant resistant against Botrytis cinerea infection, while its mechanism is unclear in ripened fruits. In this study, we investigated the chitosan effect on two type of ripened fruits including strawberry and grapes (Kyoho and Shine-Muscat) when were infected with B. cinerea. Results showed that chitosan inhibited B. cinerea growth, increased phenolic compounds and cell wall composition, modulated oxidative stress and induced jasmonic acid (JA) production in ripened fruits. Data-independent acquisition (DIA) showed that 224 and 171 proteins were upregulated 1.5-fold by chitosan in Kyoho and Shine-Muscat grape, respectively. Topless-related protein 3 (TPR3) were identified and interacted with histone deacetylase 19 (HDAC19) and negatively regulated by JA and chitosan. Meanwhile, overexpression of VvTPR3 and VvHDAC19 reduced the stability of cell wall against B. cinerea in strawberry. Taken together, chitosan induces defense related genes and protect the fruit quality against Botrytis infection through JA signaling.